IMPROVING THE MECHANISMS FOR PROVIDING ADMINISTRATIVE SERVICES BY PUBLIC AUTHORITIES IN UKRAINE - Prokopenko, Serhii (Public Management and Policy, 2026)
The development of organizational, legal, financial, personnel, information and consulting mechanisms for the provision of administrative services is one of the most important tasks for the development of public services and the formation of a service-oriented model of the state. The main goal of this article was to study the current mechanisms for the provision of administrative services in Ukraine, which are considered a set of approaches, methods, and tools for serving citizens and are aimed at changing, terminating, or acquiring the rights and obligations of individuals and legal entities in accordance with current legislation. The article uses a systematic approach to studying the organizational, legal, financial, personnel, and information and consulting mechanisms for the provision of services to citizens in Ukraine. The SWOT analysis method allowed us to identify the main strengths and weaknesses of the current mechanisms for the provision of public services in the ASC and develop recommendations for their improvement. It was found that in 2020-2025, approaches to the organization and financing of the provision of public services through the network of ASC administrative service centers changed and a decentralized management model was introduced in this area. The organization of the processes of providing public services is entirely up to the local executive authorities. Revenues to local community budgets from service fees have become the main source of covering expenses for the functioning of ASCs. Subsidies allocated from the state budget to local budgets for the construction and modernization of ASCs in 2020 were significantly lower than the amount of revenue from service fees. Since 2021, local governments have relied on their own financial resources to develop public services, which complicates their digitalization in order to simplify, ensure accessibility and speed of service. With a high level of demand for various types of services and an increasing workload on staff, there is a need to improve mechanisms for serving citizens. To do this, ASCs are implementing and developing e-services and using new methods of information support - chatbots based on artificial intelligence. At the same time, this does not solve the problem of high workload on employees, because the level of serving citizens using e-services for providing services is only 10%.